Secret powers: Acts of Googling in the therapeutic relationship. Issue 4 (15th January 2021) - Trub, Leora; Magaldi, Danielle
Abstract: Objective: The ease of online searching has diminished people's expectations of privacy and the ability to control access to information about oneself, which can alter basic assumptions about the therapy relationship. Method: This grounded theory study explored psychotherapists' experiences of searching online for patients and being searched for by patients, among 28 clinicians of primarily psychodynamic orientation. Results: Many therapists search online for information about patients, but often minimize or rationalize this action and do not share it with their patients. Meanwhile, while they believe their patients search for them, they find it difficult to raise the topic directly in therapy. Thus, when it comes to online searching and discovery of information, an air of secrecy pervades the therapeutic relationship. Conclusions: Despite the serious implications that the pervasiveness of online searching has for the treatment relationship, therapists lack sufficient support for exploring their motivations, curiosities, and urges surrounding this action.